Colourless blood fishes found while fishing north of South Georgia island in april 1978 - Maxim, Constantin (Cercetări Marine - Recherches Marines, 2026)
This paper presents the ice fishes found, while fishing with a pelagic trawl north of South Georgia Island in April 1978. Length and weight composition of the captured specimens is also presented.